Postural control of Parkinson’s disease: A visualized analysis based on Citespace knowledge graph - Li, Yan; Zheng, Jie-Jiao; Wu, Xie; Gao, Wen; Liu, Chan-Jing (Frontiers in Aging Neuroscience, 2023)
Postural control impairment is one of the primary motor symptoms in patients with Parkinson’s disease, leading to an increased risk of falling. Several studies have been conducted on postural control disorders in Parkinson’s disease patients, but no relevant bibliometric analysis has been found. In this paper, the Web of Science Core Collection database was searched for 1,295 relevant papers on postural control in Parkinson’s disease patients from December 2011 to December 2021. Based on the Citespace knowledge graph, these relevant papers over the last decade were analyzed from the perspectives of annual publication volume, countries and institutes cooperation, authors cooperation, dual-map overlay of journals, co-citation literature, and keywords. The purpose of this study was to explore the current research status, research hotspots, and frontiers in this field, and to provide a reference for further promoting the research on postural control in Parkinson’s disease patients.